2012
DOI: 10.1523/jneurosci.2162-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuronal Excitability by Interaction of Fragile X Mental Retardation Protein with Slack Potassium Channels

Abstract: Loss of the RNA-binding protein fragile X mental retardation protein (FMRP) represents the most common form of inherited intellectual disability. Studies with heterologous expression systems indicate that FMRP interacts directly with Slack Na+-activated K+channels (KNa), producing an enhancement of channel activity. We have now usedAplysiabag cell (BC) neurons, which regulate reproductive behaviors, to examine the effects of Slack and FMRP on excitability. FMRP and Slack immunoreactivity were colocalized at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 53 publications
2
114
0
Order By: Relevance
“…SLO channels contain a large intracellular Cterminal domain (Lee and Cui, 2010). Interestingly, recent studies have demonstrated that the C-terminal domain of SLACK channels, BK channel homologs that are potentiated by sodium rather than Ca 2+ , are bound to by the Fragile-X mental retardation protein in a manner that induces channel activation (Brown et al, 2010;Zhang et al, 2012). The C-terminal domain of SLO channels may similarly act as a scaffold to bind synaptic proteins that regulate AZ structure.…”
Section: Discussionmentioning
confidence: 99%
“…SLO channels contain a large intracellular Cterminal domain (Lee and Cui, 2010). Interestingly, recent studies have demonstrated that the C-terminal domain of SLACK channels, BK channel homologs that are potentiated by sodium rather than Ca 2+ , are bound to by the Fragile-X mental retardation protein in a manner that induces channel activation (Brown et al, 2010;Zhang et al, 2012). The C-terminal domain of SLO channels may similarly act as a scaffold to bind synaptic proteins that regulate AZ structure.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, apart from translational regulation, FMRP also directly binds to ion channels, which has revealed noncanonical functions. FMRP binds and activates Slack [105,106], and FMRP's association with BK channels alters their calcium sensitivity in a protein synthesis-independent manner [98,107]. A recent study also showed that FMRP interacts with the voltage-gated N-type calcium channel Ca V 2.2 and modulates its function and expression [108].…”
Section: Fmr1mentioning
confidence: 99%
“…The activity of K Na 1.1 channels can be also regulated by their interaction with other cellular proteins. These include the transmembrane protein TMEM16C (Huang et al, 2013) and the Fragile X Mental Retardation protein (Brown et al, 2010;Zhang et al, 2012b), both of which enhance K Na 1.1 channel activity. Interactions with several other cellular components, including the postsynaptic density protein PSD-95, have also been reported but their functional effects are not yet known (Uchino et al, 2003;Rizzi et al, 2015).…”
Section: The K Ca 2 Family-small Conductance Channels Regulated mentioning
confidence: 99%